God is here to stay : science, evolution, and belief in God - McFaul, Thomas R.; Brunsting, Albert, 1945- (Eugene, Oregon : Wipf & Stock, 2014)
A scientific examination in several ares across the physcial sciences and human experience to explain how the universe operates within very narrow and highly structured boundaries. Most importantly the authors created an innovative L-M confidence scale to establish confidence levels, not proofs, on how scientific discoveries impact belief in God.
Introduction: knowledge, science, and belief in God -- Humanity is structured for knowledge -- The universe is structured for conscious, self-aware life -- From non-life to life --The brain is structured for spiritual experiences -- Humanity is structured for justice -- Humanity is structured for a universal morality -- God is here to stay.
Includes bibliographical references (pages 181-185) and index.
Description based on print version record.
Keywords: God -- Proof, Empirical; God -- Proof, Moral; Religion and science; Human ecology; God -- Proof, Cosmological; Religion and science; RELIGION / General; Electronic books